Intensive Care Units Healthcare Professionals' Experiences and Negotiations at the Beginning of the COVID-19 Pandemic in Germany: A Grounded Theory Study - Madlen Hörold; Karl Philipp Drewitz; Julia Piel; Ilona Hrudey; Magdalena Rohr; Vreni Brunnthaler; Claudia Hasenpusch; Angela Ulrich; Niklas Otto; Susanne Brandstetter; Christian Apfelbacher (SAGE Publishing, 2022)
Faced with the pandemic of the novel coronavirus (SARS-CoV-2), healthcare professionals (HCPs) in intensive care units (ICU) adjusted their organizational, operational, and personal procedures to ensure care for COVID-19 patients. We used grounded theory approach to explore ICU HCPs' perspectives on professional action at the beginning of the COVID-19 pandemic in Germany from March to July 2020. The study aimed to examine implicit principles on negotiating social practice and interaction of ICU HCPs in an exceptional situation, which was characterized by a high level of changes. We conducted theme-guided qualitative telephone/virtual interviews with 39 ICU HCPs from ten German federal states. The data collection followed the principles of theoretical sampling. We adpoted grounded theory approach proposed by Charmaz and discussed using Lüscher's theoretical concept of ambivalence. The analysis revealed five interconnected categories about the ICU HCPs' negotiation of social practice and interaction at the beginning of the COVID-19 pandemic in Germany. In this context, a complex field of ambivalence (key category) emerged between habits and routines of a pre-pandemic normality. Pragmatic restructuring processes were initiated, which quickly resulted in a new normality of a "daily routine of preparation". Dealing with ambivalence offers the potential for change.